The effectiveness of a web-based education program for nurses’ self-assessed skills concerning the care of alcohol-intoxicated patients in an emergency department - Mäkelä, Kaisu-Leena; Kylmä, Jari; Noppari, Eija; Hakala, Tiina; Koivunen, Marita (Finnish Journal of eHealth and eWelfare, 2022)
The aim of this study was to measure the effectiveness of a web-based education program for nurses’ self-assessed skills concerning the care of alcohol-intoxicated patients in an emergency department. A quasi-experimental design with an intervention and comparison group was used. A quantitative approach was utilized to describe the nurses’ self-assessed skills before and after a web-based education program. Within the resources of the organization that participated in this study, it was possible to deliver the intervention to 20 nurses during one year. All ninety nurses working in the emergency department of one central hospital in Finland were randomly assigned to either the intervention group (n=20) or comparison group (n=25); in both groups, baseline (November 2017) and follow-up (December 2018) surveys were conducted before and after the intervention. The intervention group members showed a statistically significant increase in their self-assessed skills in several sections of the competence scale that was used. This may indicate that the web-based education program had a positive effect on the intervention group’s knowledge and improved their skills to care for alcohol-intoxicated patients.